Transaction cost analysis in redeveloping indigenous lands in Malaysia - Omar, Ismail (Academic Journals Database, 2009)
Land supply constraints restrict the flow of land supply onto the land market for development purposes. It disturbs the effectiveness of the land market. As a result, the underutilized area may become derelict and needs regeneration as part of urban renewal programs. The study begins with discussion on transaction costs within institutional economics analysis. In particular, the review on literature concentrates on the elements of land supply constraints with the purpose to feed the empirical analysis in the case study areas. Empirically, the study investigates sources of land supply constraints in the case study area of MAS Kampong Baru, Kuala Lumpur. Data were gathered using interviews with landowners of undeveloped and developed sites to examine why they had taken effort to develop or simply abandoned their lands undeveloped. Analysis had been undertaken using qualitative techniques on respondents using coding, either direct or indirect quotations. Landowner respondents were taken randomly to represent predetermined zones within the case study areas. Data analysed were presented in the forms of charts, histograms, diagrams and illustrations to ease discussion. One of the main findings is that landowners were unwilling to undertake redevelopment due to land supply constraints as revealed by transaction cost embedded within their status of landownership, attitudes, physical, planning and valuation or market constraints. In the end, the findings enable various interested parties to realize their roles and responsibilities in their future directions to redevelop Kampong Baru in Kuala Lumpur.